Potentialities of webQDA® for Qualitative Analysis Barriers Faced by Nurses Working in Basic Health Units - Alexandra Bulgarelli do Nascimento (2021)
Introduction: In many countries Primary Health Care (PHC) coordinates health assistance to the population and in this field, Nursing is essential area. In Brazil, we witnessed the gradual de-funding of the PHC. PHC has not received sufficient funding to fulfill the participatory mission in the Unified Health System. Nursing has limited performance because of the adoption of policies that are disjointed from the commitment to respond to health needs. Goals: To know the potential and the limits of Nursing performance at the municipal level and to recognize the potential of webQDA® for qualitative analysis of the barriers faced by nurses working in Basic Health Units (UBS). Method: Qualitative study that carried out the content analysis of Bardin, with the support of webQDA®, to unveil the meaning of the speeches from two focus groups, carried out with the collaboration of 13 nurses working in UBS in a city in São Paulo. Results and Discussion: The speeches transcribed in a word file were inserted in webQDA® as an internal source. The coding tree for the empirical categories was created, with the inclusion of the codes: ‘Identified Barriers’ and ‘Overcoming Reality’. In view of the content analysis, as recommended by Bardin, the sub-categories emerged, coded as: Identified Barriers: Work Overload, facing complex health needs and Deficit in the availability of resources; and Overcoming Reality: Nursing as a Social Practice. Conclusions: The webQDA® supported the systematization of the critical analysis of qualitative data, allowing us to note that the performance of Nursing in Basic Health Units faces barriers related to work overload, deficit in the availability of resources and response to complex needs. However, Nursing as a Social Practice has an important element to provide overcoming reality.